A Detailed Review of Data Deduplication Approaches in the Cloud and Key Challenges - Goel, Anjuli; Prabha, Chander (2023 4th International Conference on Smart Electronics and Communication (ICOSEC), 2023)
Now a day's cloud is widely used as a storage container to store an enormous amount of data. Data is growing on the cloud exponentially as every user whether an organization, business data, or end-users too, uses the cloud to back up their data. Due to this increase in demand for storing and backup data in the cloud, its performance is degrading. While sending the data on the cloud, many users send and store the same data more than one time on the cloud which results in the inefficiency of the storage system on the cloud. As a result, it is becoming difficult to manage the data on available space. Cloud vendors are finding the key to saving disk storage which maximizes disk space capacity. To avoid the storage of redundant data and to save space for upcoming data, two approaches are suggested viz. data compression and data deduplication. Deduplication is divided into various categories. Various deduplication techniques are presented under the umbrella of each category, along with their tabular comparison. These techniques are implemented to avoid redundancy still each technique has its own limitations. Although deduplication provides many solutions for not storing repeated copies yet deduplication is facing a number of challenges. It also gives useful insight into the challenges faced in the implementation of deduplication and reviews techniques and procedures for developing new deduplication strategies.